An exploration on the nexus between managers' present bias and corporate investment. Issue 2 (19th January 2022) - Kim, Huong Trang; Nguyen, Quang
ABSTRACT: This study aims to explore the role of top manager's present bias as a main driver of corporate investment. For this purpose, we embed an experiment in a firm-level panel survey with a sample of top managers from 623 textile and garment firms in Vietnam. The experiment enables us to elicit present bias for each individual manager. We find that firms led by managers with a greater level of present bias are more likely to have a lower investment. There also exists evidence that the effect of managers' present bias on corporate investment is stronger for SMEs than for large firms.